(untitled) (Research, Society and Development, 2025)
Non-compaction cardiomyopathy (NCM) is a cardiomyopathy characterized by prominent myocardial trabeculations and deep intertrabecular recesses, associated with high clinical and prognostic heterogeneity. The aim of this study is to analyze advances in diagnostic imaging methods for non-compaction cardiomyopathy, with emphasis on the contributions of echocardiography and cardiac magnetic resonance imaging, as well as to discuss their prognostic implications in clinical practice. Diagnosing this condition is a challenge, especially given the variability of morphological criteria and the overlap with physiological patterns of ventricular trabeculation. In this context, cardiovascular imaging methods play a central role in the identification, characterization, and risk stratification of patients. Echocardiography remains the initial assessment tool, while cardiac magnetic resonance imaging stands out for its greater diagnostic accuracy and tissue characterization capabilities, including the detection of myocardial fibrosis through late gadolinium enhancement. Recent advances, such as myocardial strain analysis, three-dimensional techniques, and artificial intelligence applications, have contributed to greater diagnostic accuracy and better prognostic assessment. The integration of structural, functional, and tissue parameters has proven fundamental in differentiating benign forms from presentations associated with a higher risk of heart failure, arrhythmias, and adverse cardiovascular events, reinforcing the importance of a multiparametric approach in the management of non-compaction cardiomyopathy.